Investors Attitudes towards Stock Market Investment - Kavitha, C. (International Journal of Scientific Research and Management (IJSRM), 2015)
The researcher was inspired by the persistent lack of local investors participating on the National Stock Exchange (NSE), the wide spread ignorance about financial assets and the continuous purchase of stocks with no information known about them by most people in the country plus the wide gap between the rich who invest in stocks and the poor who continuously make losses in the real investment industry. The study was guided by objectives with a purpose of tracking investor’s attitudes and perceptions towards stock market investments A sample of 125 respondents was used and the findings analyzed using SPSS. The study used a cross-sectional survey design and with application of quantitative and qualitative data. The study may also use descriptive and correlation approaches to establish the relationships amongst the study variables. The study made several recommendations among which to increase investor awareness as a means of encouraging local investors to list on the stock exchange. The regulatory authorities should improve on their performance in order to increase the confidence of the local investor. Furthermore they should introduce investor incentives to boost the volumes traded on the exchange with a review of The stock market regulations with a view to make them stronger and more attractive to local investors.